Effects of Geraniol on Survival, Reproduction, Endophytes, and Transcriptome of Tea Green Leafhoppers (Empoasca onukii) - Junjie Tian; Hainuo Hong; Shiliang Mo; Shiqin Mo; Hongliang Shi; Juan Shi; Ying Zhou (Agronomy)
Herbivore-induced plant volatiles (HIPVs) serve as powerful defense mechanisms that help plants mitigate pest-induced stress. Geraniol is a HIPV released by tea leaves in response to damage inflicted by tea green leafhoppers. In order to investigate whether the release of geraniol is a defensive mechanism of tea plants against infestation by tea green leafhoppers, our study explored the effects of geraniol on tea green leafhoppers, including the selectivity of tea green leafhoppers’ response to geraniol, survival and reproductive parameters, as well as alterations in endophytes and the transcriptome. The findings indicated that while geraniol did not exhibit strong repellent or lethal effects on tea green leafhoppers, it significantly reduced the egg-laying and hatching rates. Through 16S rRNA microbial sequencing, we found that geraniol treatment significantly altered the composition of endophytic microbial communities in tea green leafhoppers, potentially affecting their metabolic functions. Transcriptome analysis further showed that genes associated with energy metabolism, such as glutamate dehydrogenase, were significantly upregulated in response to geraniol, suggesting that tea green leafhoppers may enhance energy metabolism to counteract geraniol-induced stress. Additionally, the downregulation of antimicrobial peptide-related signaling pathways suggests that geraniol may weaken the immune capacity of tea green leafhoppers, potentially reducing their resistance to pathogens. These findings indicate that the strategic application of geraniol could be a promising approach to controlling tea green leafhopper populations. This study enhances our understanding of the insect-resistant mechanisms of HIPVs and provides new insights into environmentally sustainable pest management strategies for tea plantations.